2023
DOI: 10.1371/journal.pone.0286085
|View full text |Cite
|
Sign up to set email alerts
|

The development of adolescents’ loneliness during the COVID-19 pandemic: The role of peer status and contact with friends

Abstract: The COVID-19 measures raised societal concerns about increases in adolescents’ loneliness. This study examined trajectories of adolescents’ loneliness during the pandemic, and whether trajectories varied across students with different types of peer status and contact with friends. We followed 512 Dutch students (Mage = 11.26, SD = 0.53; 53.1% girls) from before the pandemic (Jan/Feb 2020), over the first lockdown (March-May 2020, measured retrospectively), until the relaxation of measures (Oct/Nov 2020). Laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Students' lower levels of loneliness following a school transition were in line with some previous studies (Barber & Olsen, 2004;Lorijn et al, 2023). Yet, the results show a more positive view of school transitions than most previous studies (Jindal-Snape et al, 2020).…”
Section: (Dis)continuation Of Peer Experiencessupporting
confidence: 90%
See 3 more Smart Citations
“…Students' lower levels of loneliness following a school transition were in line with some previous studies (Barber & Olsen, 2004;Lorijn et al, 2023). Yet, the results show a more positive view of school transitions than most previous studies (Jindal-Snape et al, 2020).…”
Section: (Dis)continuation Of Peer Experiencessupporting
confidence: 90%
“…In a recent review on school transitions, ten studies reported a negative impact of the transition on their peer experiences, whereas seven studies reported an improvement in peer experiences (Jindal-Snape et al, 2020). For instance, in contrast to the previous mentioned study showing stability in loneliness (Kingery et al, 2011), other studies found that loneliness increased following a school transition (Benner et al, 2017;Benner & Graham, 2009), decreased (Lorijn et al, 2023), or increased or decreased depending on the school transition (i.e., elementary to middle school vs. middle to high school; Barber & Olsen, 2004). Moreover, whereas most students who structurally transitioned to high school in the U.S.A. were more likely to have fewer friends and become isolated than students who did not transition, some students gained friends (Felmlee et al, 2018;Temkin et al, 2018).…”
Section: (Dis)continuation Of Peer Experiences Across School Transitionsmentioning
confidence: 94%
See 2 more Smart Citations